Peran Modal Sosial Santri dalam Menghadapi Dampak Globalisasi: Studi Kasus di Pondok Pesantren Buntet - Margi Wahono; Dasim Budimansyah; Elly Malihah; Susan Fitriasari (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
Islamic boarding schools in Indonesia face major challenges due to the Industrial Revolution 4.0 and globalization, which include adaptation to digital technology, expansion of social networks, and integration of Islamic boarding school values in technology-based curricula. This research focuses on the role of social capital in maintaining the relevance of Islamic boarding schools, with Buntet Islamic Boarding School as a case study. Using a qualitative approach with in-depth interviews and participant observation, data was analyzed to identify the daily application of social capital. Findings show that strong social networks, mutual trust, internalized social norms, and cooperation play key roles in the transformation of Islamic boarding schools. The uniqueness of the Buntet Islamic Boarding School can be seen in its ability to build a strong alumni network, facilitate access to new resources, and maintain the identity and values of the Islamic boarding school through a technology-based curriculum. The results of this research have practical implications in the context of education in Indonesia, guiding Islamic boarding schools and other traditional institutions to integrate social capital in their adaptation strategies to face the impacts of the Industrial Revolution 4.0 and globalization, maintain sustainability, and increase competitiveness.